SAFE ELECTROSURGERY USE: KNOWLEDGE, ATTITUDES AND PRACTICES OF SURGICAL TRAINEES - Khan, Mahmood Ahmed; Siddiqui, Sheeraz Shakoor; Zubair, Muhammad (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the knowledge, attitudes and practices of general surgical trainees regarding safe use of diathermy. Methodology: In this cross-sectional Survey, 47 surgical trainees of the Civil Hospital Karachi, comprising PGY 1 through 4, were interviewed by questionnaires made up of five close-ended and three open-ended items. Results: Majority of the trainees belonged to the first two years of training. More than 80% had no formal training in diathermy use. Most of them were found lacking in core knowledge and evidence-based practice of electrosurgery. Conclusion: There was a high level of ignorance regarding current and established principles of diathermy use among surgical trainees at the Civil Hospital Karachi.